Wae Bobok Tourism Potential: Mapping a Destination in West Manggarai, East Nusa Tenggara - L. K. Herindiyah Kartika Yuni; I Wayan Kartimin (Soshum: Jurnal Sosial dan Humaniora, 2024)
West Manggarai is one of the districts in East Nusa Tenggara that has been visited by tourists, unfortunately, the purpose of the visit is dominant to the city of Labuan Bajo. Many tourism potentials in West Manggarai have been known, widely praised, and researched but Wae Bobok and its potential have not yet been published. Wae Bobok is a forest area located in the Tanjung Boleng Tourism Village area. The need for identification and mapping of potential is very essential to be better known by the wider community so that can achieve an equal visit and income. Mapping is carried out with a spatial analysis, which is an approach in geography to analyze and describe the geographical distribution of tourism data. The study’s purpose is to identify (1) the tourism potential of Wae Bobok as a tourist destination, (2) the mapping of Wae Bobok as a tourist destination (3) the strengths, weaknesses, opportunities, and threats of Wae Bobok.  Data were analyzed using qualitative analysis techniques. This research resulted: in (1) the tourism potential of Wae Bobok as a tourist destination, (2) Wae Bobok has been mapped into natural, cultural, and adventure tourism attractions based on its natural potential and resources. (3) SWOT analysis of Wae Bobok includes strengths; natural, cultural, and artificial attractions, strategic location and accessibility, available supporting facilities, and local products, managed by pokdarwis. Weaknesses; human resources quality, cleanliness, local guides, tour packages, and internet network. Opportunities: position, special segment, local support, but the existence of competitors and Prone to natural disasters and flooding is a threat to Wae Bobok.